2009
DOI: 10.1002/chem.200900470
|View full text |Cite
|
Sign up to set email alerts
|

The Three‐Component Biginelli Reaction: A Combined Experimental and Theoretical Mechanistic Investigation

Abstract: Biginelli reactions have been monitored by direct infusion electrospray ionization mass spectrometry (ESI-MS) and key cationic intermediates involved in this three-component reaction have been intercepted and further characterized by tandem MS experiments (ESI-MS/MS). Density functional theory calculations were also used to investigate the feasibility of the major competing mechanisms proposed for the Biginelli reaction. The experimental and theoretical results were found to corroborate the iminium mechanism p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(57 citation statements)
references
References 66 publications
2
52
0
3
Order By: Relevance
“…16 It is worth noting that, just like De Souza et al, 14 the authors noted the presence of a dormant intermediate of m/z 237 (see the structure in Scheme 12) which is in accordance with the Knoevenagel reaction pathway. However, all other detected and characterized intermediates were in accordance with the N-acyliminium mechanism re-examined by Kappe;12 and no other Knoevenagel-based intermediate could be detected during the reaction time monitoring.…”
Section: The Biginelli Multicomponent Reactionsupporting
confidence: 67%
See 1 more Smart Citation
“…16 It is worth noting that, just like De Souza et al, 14 the authors noted the presence of a dormant intermediate of m/z 237 (see the structure in Scheme 12) which is in accordance with the Knoevenagel reaction pathway. However, all other detected and characterized intermediates were in accordance with the N-acyliminium mechanism re-examined by Kappe;12 and no other Knoevenagel-based intermediate could be detected during the reaction time monitoring.…”
Section: The Biginelli Multicomponent Reactionsupporting
confidence: 67%
“…Curiously, DFT calculations for the Knoevenagel mechanism revealed the highest energy barrier in accordance with MS data. Based on the data obtained by this landmark work, 14 the authors could suggest that the iminium pathway (as proposed by Kappe 12 ) is highly favoured and the enamine and Knoevenagel pathways could be kinetically discarded. A recent report questioned the conclusions that Lewis acids may prefer the enamine-like reaction pathway.…”
Section: The Biginelli Multicomponent Reactionmentioning
confidence: 99%
“…72 ESI-MS(/MS) has been proved to be an outstanding tool for reaction mechanism monitoring [73][74][75] with impressive results for the Biginelli reaction. 76,77 We have already used ESI-MS(/MS) as an unsurpassed tool in the mechanistic investigation of the Biginelli reaction. [39][40][41] ESI-MS(/MS) online monitoring was therefore used to investigate the mechanism of the Biginelli reaction using catalyst 1.…”
Section: Resultsmentioning
confidence: 99%
“…Latter on, de Souza and colleagues studied the mechanism of Biginelli reaction with mass spectrometry by direct infusion electrospray (electron-spray ionization mass spectroscopy, ESI-MS) [8]. In their studies, they found that reacting benzaldehyde and urea leads to the formation of ions of m/z 209, 167, and 149 ( Figure 4).…”
Section: Introductionmentioning
confidence: 99%